2013
DOI: 10.1016/j.hoc.2012.10.004
|View full text |Cite
|
Sign up to set email alerts
|

ELANE Mutations in Cyclic and Severe Congenital Neutropenia

Abstract: There are two main forms of hereditary neutropenia: cyclic and severe congenital neutropenia (SCN). Cyclic neutropenia is an autosomal dominant disorder in which neutrophil counts fluctuate between nearly normal levels and close to zero with 21-day periodicity. In contrast, SCN, also known as Kostmann syndrome, consists of chronic and profound neutropenia, with a characteristic promyelocytic maturation arrest in the bone marrow. Unlike cyclic neutropenia, SCN displays frequent acquisition of somatic mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 130 publications
(157 reference statements)
1
105
0
2
Order By: Relevance
“…Individuals with SCN have myeloid hypoplasia with arrest of myelopoiesis at the promyelocyte/myelocyte stage (2). Current treatment by administration of high-dose granulocyte CSF (G-CSF) induces an increase in the neutrophil counts in the peripheral blood (PB) of most SCN patients.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with SCN have myeloid hypoplasia with arrest of myelopoiesis at the promyelocyte/myelocyte stage (2). Current treatment by administration of high-dose granulocyte CSF (G-CSF) induces an increase in the neutrophil counts in the peripheral blood (PB) of most SCN patients.…”
Section: Introductionmentioning
confidence: 99%
“…5 Although the genetic evidence that ELANE mutations are causative to SCN and CyN is compelling, it is far from clear how they contribute to the chronic or cyclic episodes of severe neutropenia. 6,7 Initially it was thought that the ELANE mutations in CyN were distinct from, and more "benign" than, those found in SCN mutations. However, later studies in extended patient series showed that, although there are trends in the spectrum of ELANE mutations toward either SCN or CyN, there is also a significant overlap.…”
Section: Scn With Mutations In Elane (Elane-scn)mentioning
confidence: 99%
“…Postulated mechanisms include: (1) altered function through mutant NE mislocalization (ie, granular versus membrane-proximal); (2) altered biochemical properties affecting substrate specificities of the mutant NE; and (3) protein misfolding in the endoplasmic reticulum (ER), triggering an unfolded protein response (UPR). 7 Given the mutation diversity, none of these potential explanations can be held responsible for causing neutropenia in all patients. Complicating matters even further, SCN patients have been reported in which ELANE expression in the myeloid progenitors (promyelocyte, myelocytes, metamyelocytes) is severely down-regulated, casting doubts on whether the mutant NE protein contributed at all to the neutropenia in these cases.…”
Section: Scn With Mutations In Elane (Elane-scn)mentioning
confidence: 99%
“…19 Neutrophil elastase is also a potent activator of eosinophils. 20 Since neutrophil cycling was observed in all four subjects with definite EAE and preceded the eosinophilia in two subjects, the coding regions of ELANE were sequenced using DNA from three subjects and two normal controls.…”
Section: Cd4mentioning
confidence: 99%